2017
DOI: 10.1155/2017/5796456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Carbohydrate-Rich Diet on Rat Detrusor Smooth Muscle Contractility: An Experimental Study

Abstract: Objectives We aimed to investigate the effect of a carbohydrate-rich diet on detrusor contractility in rats. Materials and Methods Sprague-Dawley rats were randomized into two groups. The control group received regular food and water. The study group received carbohydrate-rich diet for six weeks. The rats' detrusor muscle was isolated for pharmacological and histopathological examinations. Results In the control and study groups, mean body weights were 431.5 ± 27.6 g and 528.0 ± 36.2 g, respectively (p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that MET has a protective effect against cyclophosphamideinduced cystitis in mice (13). Bladder dysfunction is very common in diabetes mellitus (14) and obesity (15). Various clinical studies have shown that bladder dysfunctions in diabetic patients, such as detrusor overactivity, impaired detrusor contractility and reflex activity (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that MET has a protective effect against cyclophosphamideinduced cystitis in mice (13). Bladder dysfunction is very common in diabetes mellitus (14) and obesity (15). Various clinical studies have shown that bladder dysfunctions in diabetic patients, such as detrusor overactivity, impaired detrusor contractility and reflex activity (14).…”
Section: Introductionmentioning
confidence: 99%